ANALYSIS OF THE INFLUENCE OF COMFORT AND INCENTIVES ON EMPLOYEE WORK ETHICS AT GRAHA MEKAR SEHATI WEST OKU COOPERATIVE - Garaika Hamzah; Winda Feriyana; Endang Sri Mulatsih (STIE Trisna Negara OKU Timur, 2022)
This study aims to analyze partially or jointly the effect of comfort, incentives on employee work ethic and analyze the most dominant variable in influencing employee work ethic at Graha Mekar Sehati Cooperative West OKU. The results of the regression analysis and the correlation between comfort and employee work ethic show the regression model Ŷ = 0.076 + 0.989X1 + e with a correlation coefficient of 0.809. The results of the regression analysis and the correlation between incentives and work ethic show that the regression model is Ŷ = 24.642 + 0.581X2 + e with a correlation coefficient of 0.466. The results of multiple regression analysis and the correlation between Comfort and Incentives together on Work Ethics show the regression model Ŷ = 1.096 + 0.954X1 + 0.068X2 + e with a correlation coefficient of 0.811. From the multiple linear regression equation above, it shows that the comfort variable (X1) is higher dominant influence on employee work ethic compared to incentives. This research was conducted on 30 respondents with the analytical method used is path analysis using SPSS software.